Silicon dioxide particles and method for producing the same, silica sol, polishing composition, polishing method, method for producing semiconductor wafers, and method for producing semiconductor devices
By optimizing the d-value and surface silanol-based density of silica particles and carrying out pressurized heating treatment, the problem of insufficient condensation degree of existing silica particles is solved, and higher mechanical strength and storage stability are achieved, and suitable for efficient grinding and semiconductor manufacturing.
Patent Information
- Application Number
- CN202080014939.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-21
- Filing Date
- 2020-02-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2040-02-19
AI Technical Summary
The existing silica particles obtained by hydrolysis and condensation reaction of alkoxysilane are insufficient in the condensation degree, resulting in poor mechanical strength and deterioration of storage stability, and are easily destroyed during the grinding process.
By optimizing the d-value measured by wide-angle X-ray scattering and the surface silanol-based density determined by the Sears method, combined with pressurized heating treatment, the condensation degree and mechanical strength of the silica particles are improved.
It significantly improves the grinding characteristics and storage stability of silica particles, enhances mechanical strength, reduces damage during the grinding process, and improves the manufacturing efficiency of semiconductor wafers and devices.
Smart Images

Figure CN113454024B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to silicon dioxide particles and a method for producing the same, a silica sol, an abrasive composition, a polishing method, a method for producing a semiconductor wafer, and a method for producing a semiconductor device. Background Art
[0002] As a method for polishing the surface of materials such as metals and inorganic compounds, polishing methods using polishing liquids are known. Among them, in chemical mechanical polishing (CMP) such as final processing polishing of original silicon wafers for semiconductors and their regenerated silicon wafers, flattening of interlayer insulating films, formation of metal plugs, and formation of embedded wiring during semiconductor device manufacturing, the surface state has a great influence on semiconductor characteristics, so the surfaces and end faces of these components are required to be polished with extremely high precision.
[0003] In such precision grinding, an abrasive composition containing silica particles is used, and colloidal silica is widely used as its main component, i.e., abrasive particles. Regarding colloidal silica, colloidal silica (fumed silica, etc.) obtained by thermal decomposition of silicon tetrachloride, colloidal silica obtained by deionization of alkali metal silicates such as water glass, colloidal silica obtained by hydrolysis reaction and condensation reaction of alkoxysilane (commonly referred to as "sol-gel method"), etc. are known, depending on the production method.
[0004] A lot of research has been conducted so far on the production method of colloidal silica. For example, Patent Documents 1 to 3 disclose methods for producing silica particles by using the hydrolysis reaction and condensation reaction of alkoxysilane. Patent Document 4 discloses a method for producing silica particles by performing a heat treatment under alkaline conditions after the hydrolysis reaction and condensation reaction of alkoxysilane. Patent Document 5 discloses a method for producing silica particles by performing a heat treatment under acidic conditions after the hydrolysis reaction and condensation reaction of alkoxysilane.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 11-60232
[0008] Patent Document 2: International Publication No. 2008 / 123373
[0009] Patent Document 3: International Publication No. 2008 / 015943
[0010] Patent Document 4: Japanese Patent Application Publication No. 2010-83744
[0011] Patent Document 5: Japanese Patent Application Publication No. 2018-90798 Summary of the invention
[0012] Problems to be solved by the invention
[0013] However, in general, the silica particles in the silica sol obtained by the hydrolysis reaction and condensation reaction of alkoxysilane cannot be said to have a sufficiently high degree of condensation. The reason for this is believed to be that the hydrolysis reaction and the condensation reaction proceed simultaneously, and the alkoxy group or silanol group is likely to remain. In silica particles with a low degree of condensation, SiO 4 The formation of the ring that tetrahedron is connected and constitutes is insufficient, and the ring size is small, deformation is large, and mechanical strength is poor. If the silicon dioxide particles with such low condensation degree are used for grinding, the silicon dioxide particles are destroyed during grinding, and the destroyed silicon dioxide particles can be produced in grinding and adhere to the adverse effects such as the ground body. In addition, in the silicon dioxide particles with low condensation degree, silanol groups remain in a large number, so the silanol groups remaining during preservation become reactive sites, which deteriorates storage stability.
[0014] It is believed that in the methods for producing silica sol by hydrolysis reaction and condensation reaction of alkoxysilane disclosed in Patent Documents 1 to 3, the obtained silica sol is not subjected to a treatment such as pressurization and heating treatment to increase the condensation degree of silica particles, and the obtained silica particles have insufficient ring formation, large deformation, poor mechanical strength, and poor storage stability. In addition, the silica particles obtained by the methods disclosed in Patent Documents 4 and 5 also have poor mechanical strength and poor storage stability, and heating treatment under acidic conditions or alkaline conditions may cause aggregation of silica particles and destruction of the silica skeleton.
[0015] The present invention is made in view of such problems, and an object of the present invention is to provide silicon dioxide particles having excellent polishing properties and storage stability, a method for producing the same, a silica sol, and a polishing composition. In addition, another object of the present invention is to provide a polishing method having excellent productivity of a polished body, a method for producing a semiconductor wafer, and a method for producing a semiconductor device.
[0016] Means for solving problems
[0017] Conventional silica particles, especially silica particles obtained by hydrolysis and condensation of alkoxysilane, have not necessarily been found to have sufficient grinding properties and storage stability. However, the present inventors have repeatedly conducted in-depth studies and found that the grinding properties and storage stability of silica particles can be improved by optimizing the d value measured by wide-angle X-ray scattering, thereby completing the present invention.
[0018] That is, the gist of the present invention is as follows.
[0019] [1] A silica particle, wherein the d value measured by wide-angle X-ray scattering is When , the following formula (1) is satisfied:
[0020] y ≥ 4.2 (1).
[0021] [2] The silica particles according to [1] above, wherein the surface silanol group density measured by the Sears method is x number / nm 2 When the above-mentioned d value and the above-mentioned surface silanol group density satisfy the following formula (2),
[0022] y≥-0.2x+5.4 (2).
[0023] [3] The silica particles according to [1] or [2], wherein the d value and the surface silanol group density measured by the Sears method are x / nm 2 The surface silanol group density further satisfies the following formula (3) and the following formula (4),
[0024] y≤6.0 (3)
[0025] y≤-0.2x+7.0 (4).
[0026] [4] The silica particles according to any one of [1] to [3] above, wherein the average primary particle size measured by the BET method is 10 nm to 60 nm.
[0027] [5] The silica particles according to any one of [1] to [4] above, wherein the average secondary particle size measured by DLS method is 20 nm to 100 nm.
[0028] [6] The silica particles according to any one of [1] to [5] above, wherein the metal impurity content is 5 ppm or less.
[0029] [7] The silica particles according to any one of [1] to [6] above, wherein the main component is a tetraalkoxysilane condensate.
[0030] [8] The silica particles according to [7] above, wherein the tetraalkoxysilane condensate comprises a tetramethoxysilane condensate.
[0031] [9] A method for producing silica particles, comprising subjecting silica particles to a pressure-heat treatment to obtain the silica particles according to any one of [1] to [8].
[0032]
[10] A silica sol comprising the silica particles according to any one of [1] to [8] above.
[0033]
[11] The silica sol according to
[10] above, wherein the content of the silica particles in the total amount of the silica sol is 3% by mass to 50% by mass.
[0034]
[12] A polishing composition comprising the silica sol described in
[10] or
[11] above.
[0035]
[13] A polishing method comprising polishing using the polishing composition described in
[12] .
[0036]
[14] A method for producing a semiconductor wafer, comprising the step of polishing using the polishing composition described in
[12] above.
[0037]
[15] A method for manufacturing a semiconductor device, comprising the step of performing polishing using the polishing composition described in
[12] .
[0038] Effects of the Invention
[0039] The silica particles of the present invention, the silica particles obtained by the production method of the present invention, the silica sol of the present invention, and the polishing composition of the present invention are excellent in polishing properties and storage stability. In addition, in the polishing method of the present invention, the production method of a semiconductor wafer of the present invention, and the production method of a semiconductor device of the present invention, the productivity of the object to be polished is excellent. DETAILED DESCRIPTION
[0040] The present invention is described in detail below, but the present invention is not limited to the following embodiments and can be implemented with various modifications within the scope of the gist thereof. It should be noted that when the expression "to" is used in this specification, it is used as an expression including the numerical values or physical property values before and after it.
[0041] (Silicon dioxide particles)
[0042] Regarding the silica particles according to the present embodiment, the d value measured by wide-angle X-ray scattering is defined as When the following formula (1) is satisfied.
[0043] y ≥ 4.2 (1)
[0044] If the d value of the silica particle is Above, in the shared SiO 4 The formation of tetrahedral oxygen simultaneous rings is promoted, the ring size becomes larger, the deformation becomes smaller, the silica particles are less likely to be elastically deformed, the mechanical strength is excellent, and the polishing properties of the polishing composition are excellent.
[0045] The d value of the silica particles is determined by using copper Kα rays (Kα1 rays with a wavelength of ), calculated using the first sharp diffraction peak (FSDP) measured by wide-angle X-ray scattering. That is, it is a value calculated by calculating the scattering vector q (q = 4π·sinθ / λ) based on the scattering angle 2θ showing the maximum intensity of the observed halo pattern, and using the scattering vector q, using the following formula (5) representing the Bragg formula (λ = 2d·sinθ). In the case of amorphous silica, this d value represents the interval between the surfaces aligned across the gap.
[0046] d=2π / q···(5)
[0047] Specifically, a parallel beam X-ray diffraction device was used, and a silica sol containing silica particles was filled into the concave part of a silicon non-reflective sample plate and installed in the device. ) was irradiated to the silica sol on the non-reflective sample plate at an irradiation angle of 0.1°, and 2θ scanning (2θ range was 5° to 50°) was performed to obtain an X-ray scattering pattern. The scattering angle 2θ showing the maximum intensity of the obtained halo pattern was recorded, and the scattering vector q (q = 4π·sinθ / λ) was calculated. Using the scattering vector q, the above formula (5) representing the Bragg formula (λ = 2d·sinθ) was used to calculate the d value.
[0048] Regarding the d value of the silica particles, in view of the large ring size, few defects, excellent mechanical strength of the silica particles, and excellent polishing properties of the polishing composition, the silica particles satisfy the following formula (1), preferably satisfy the following formula (1'), more preferably satisfy the following formula (1"), and further preferably satisfy the following formula (1'").
[0049] y ≥ 4.2 (1)
[0050] y≥4.5 (1')
[0051] y≥4.7 (1”)
[0052] y≥4.8 (1”')
[0053] The d value of the silica particles preferably satisfies the following formula (3), more preferably satisfies the following formula (3'), and even more preferably satisfies the following formula (3") from the viewpoint that the silica particles maintain an amorphous shape and form a ring with little deformation.
[0054] y≤6.0 (3)
[0055] y≤5.8 (3')
[0056] y≤5.7 (3”)
[0057] The d value of the silica particles can be set to a desired range by adjusting the conditions of the hydrolysis reaction and condensation reaction of the alkoxysilane and the subsequent treatment conditions. Specifically, methods include: pressurizing and heating the silica sol obtained by the hydrolysis reaction and condensation reaction of the alkoxysilane; performing a hydrolysis reaction and a condensation reaction separately; adding a reaction accelerator to the hydrolysis reaction and the condensation reaction. Among these methods, the method of pressurizing and heating the silica sol obtained by the hydrolysis reaction and the condensation reaction of the alkoxysilane is preferred in view of the ability to accurately control the d value.
[0058] Regarding the silica particles, when the surface silanol group density measured by the Sears method is x number / nm 2 , the d value measured by wide-angle X-ray scattering is set to When the following formula (1) and the following formula (2) are satisfied, the following formula (1) and the following formula (2) are preferably satisfied. 4 The formation of tetrahedral oxygen simultaneous rings is promoted, the silica particles have few defects, the silica particles are excellent in mechanical strength, the polishing properties of the polishing composition are excellent, and the silica particles have appropriate surface repulsion, and the dispersion stability of the silica sol is excellent.
[0059] y ≥ 4.2 (1)
[0060] y≥-0.2x+5.4 (2)
[0061] The silica particles more preferably satisfy the following formula (3) and the following formula (4). If the following formula (3) and the following formula (4) are satisfied, the ring size is large, the deformation is small, the mechanical strength of the silica particles is excellent, the polishing properties of the polishing composition are excellent, and the silica particles have appropriate surface repulsion, which can inhibit the aggregation of silica sol.
[0062] y≤6.0 (3)
[0063] y≤-0.2x+7.0 (4)
[0064] The surface silanol group density of the silica particles was measured by the Sears method. Specifically, it was measured and calculated under the following conditions.
[0065] Collect silica sol equivalent to 1.5g of silica particles, add pure water to make the liquid volume 90mL. Under 25°C environment, add 0.1mol / L hydrochloric acid aqueous solution until the pH becomes 3.6, add 30g of sodium chloride, slowly add pure water while completely dissolving the sodium chloride, and add pure water until the total amount of the final test solution becomes 150mL to obtain the test solution.
[0066] The obtained test solution was added to an automatic titrator, and a 0.1 mol / L sodium hydroxide aqueous solution was added dropwise, and the titration amount A (mL) of the 0.1 mol / L sodium hydroxide aqueous solution required to increase the pH from 4.0 to 9.0 was measured.
[0067] The consumption V (mL) of 0.1 mol / L sodium hydroxide aqueous solution required to increase the pH of 1.5 g of silica particles from 4.0 to 9.0 was calculated using the following formula (6). The surface silanol group density ρ (number / nm) of silica particles was calculated using the following formula (7). 2 ).
[0068] V=(A×f×100×1.5) / (W×C)···(6)
[0069] A: The titration amount of 0.1 mol / L sodium hydroxide aqueous solution required to increase the pH from 4.0 to 9.0 for 1.5 g of silica particles (mL)
[0070] f: Titer of the 0.1 mol / L sodium hydroxide aqueous solution used
[0071] C: Concentration of silica particles in silica sol (mass %)
[0072] W: The amount of silica sol collected (g)
[0073] ρ=(B×N A ) / (10 18 ×M×S BET )···(7)
[0074] B: The amount of sodium hydroxide (mol) required to adjust the pH of 1.5 g of silica particles from 4.0 to 9.0, calculated from V
[0075] N A : Avogadro constant (unit / mol)
[0076] M: Silica particle amount (1.5 g)
[0077] S BET : Specific surface area of silica particles measured when calculating the average primary particle size (m 2 / g)
[0078] It should be noted that the determination and calculation method of the surface silanol group density of the aforementioned silica particles refer to "G.W. Ears, Jr., Analytical Chemistry, Vol. 28, No. 12, pp. 1981-1983 (1956)", "Shinichi Hanaba, Development of abrasives for semiconductor integrated circuit processes, doctoral thesis of Kochi Institute of Technology, pp. 39-45, March 2004", "Japanese Patent No. 5967118", and "Japanese Patent No. 6047395".
[0079] The d value and surface silanol group density of the silica particles can be set to a desired range by adjusting the conditions of the hydrolysis reaction and condensation reaction of the alkoxysilane and the subsequent treatment conditions. Specifically, methods such as pressurizing and heating the silica sol obtained by the hydrolysis reaction and condensation reaction of the alkoxysilane; adding a reaction accelerator to the hydrolysis reaction and condensation reaction can be cited. Among these methods, from the perspective of being able to accurately control the d value and the surface silanol group density, a method of pressurizing and heating the silica sol obtained by the hydrolysis reaction and condensation reaction of the alkoxysilane is preferred.
[0080] The hydrolysis reaction and condensation reaction are methods of hydrolyzing alkoxysilane in the presence of a catalyst such as an acid or base, causing the generated silanol groups to dehydrate and condense to form siloxane bonds, while causing the particles to grow to obtain silica particles. At this time, the silanol groups gradually disappear as the condensation reaction proceeds, but the density of silanol groups inside and on the surface of the silica particles can be adjusted by setting conditions such as the composition of the alkoxysilane, solvent or dispersion medium, catalyst, reaction temperature, reaction time, etc. during the hydrolysis reaction and condensation reaction.
[0081] The silica particles preferably satisfy the following formula (8), more preferably satisfy the following formula (8'), and even more preferably satisfy the following formula (8"), from the viewpoint that the silica particles have appropriate surface repulsion and the silica sol has excellent dispersion stability.
[0082] x ≥ 0.1 (8)
[0083] x ≥ 0.5 (8')
[0084] x≥1 (8”)
[0085] The silica particles preferably satisfy the following formula (9), more preferably satisfy the following formula (9'), and even more preferably satisfy the following formula (9"), from the viewpoint that the silica particles have appropriate surface repulsion and can suppress aggregation of the silica particles.
[0086] x≤10 (9)
[0087] x≤7.5 (9')
[0088] x≤7 (9”)
[0089] The silica particles preferably satisfy the following formula (2), more preferably satisfy the following formula (2'), and even more preferably satisfy the following formula (2"), from the perspectives of large ring size, small deformation, excellent mechanical strength of the silica particles, and excellent polishing properties of the polishing composition.
[0090] y≥-0.2x+5.4 (2)
[0091] y≥-0.2x+5.5 (2')
[0092] y≥-0.2x+5.6 (2”)
[0093] The silica particles preferably satisfy the following formula (4), and more preferably satisfy the following formula (4'), from the viewpoint of forming a ring with a small deformation while maintaining an amorphous shape.
[0094] y≤-0.2x+7.0 (4)
[0095] y≤-0.2x+6.9 (4')
[0096] The average primary particle size of the silica particles is preferably 5 nm or more, more preferably 10 nm or more, and preferably 100 nm or less, more preferably 60 nm or less. If the average primary particle size of the silica particles is 5 nm or more, the storage stability of the silica sol is excellent. In addition, if the average primary particle size of the silica particles is 100 nm or less, the surface roughness and damage of the polished body represented by the silicon wafer can be reduced, and the sedimentation of the silica particles can be suppressed.
[0097] The average primary particle size of the silica particles was measured by the BET method. Specifically, the specific surface area of the silica particles was measured using an automatic specific surface area measuring device, and the average primary particle size was calculated using the following formula (10).
[0098] Average primary particle size (nm) = 6000 / (specific surface area (m 2 / g)×density(g / cm 3 ))···(10)
[0099] The average primary particle size of the silica particles can be adjusted to a desired range according to known conditions and methods.
[0100] The average secondary particle size of the silica particles is preferably 10 nm or more, more preferably 20 nm or more, and preferably 200 nm or less, more preferably 100 nm or less. If the average secondary particle size of the silica particles is 10 nm or more, the removal of particles and the like during cleaning after grinding is excellent, and the storage stability of the silica sol is excellent. If the average secondary particle size of the silica particles is 200 nm or less, the surface roughness and damage of the grinding body represented by the silicon wafer during grinding can be reduced, the removal of particles and the like during cleaning after grinding is excellent, and the sedimentation of the silica particles can be suppressed.
[0101] The average secondary particle size of the silica particles is measured by the DLS method. Specifically, it is measured using a dynamic light scattering particle size measuring apparatus.
[0102] The average secondary particle size of the silica particles can be adjusted to a desired range according to known conditions and methods.
[0103] The cv value of the silica particles is preferably 15 or more, more preferably 20 or more, further preferably 25 or more, and preferably 50 or less, more preferably 40 or less, and further preferably 35 or less. If the cv value of the silica particles is 15 or more, the polishing rate of the polished body represented by the silicon wafer is excellent, and the productivity of the silicon wafer is excellent. In addition, if the cv value of the silica particles is 50 or less, the surface roughness and damage of the polished body represented by the silicon wafer can be reduced during polishing, and the removal of particles, etc. is excellent during cleaning after polishing.
[0104] The cv value of silica particles is a value calculated by measuring the average secondary particle size of silica particles using a dynamic light scattering particle size analyzer and using the following formula (11), and is a value that serves as an indicator of uniform particle size.
[0105] cv value = (standard deviation (nm) / average secondary particle size (nm)) × 100... (11)
[0106] The agglomeration ratio of the silica particles is preferably 1.0 or more, more preferably 1.1 or more, and preferably 4.0 or less, more preferably 3.0 or less. If the agglomeration ratio of the silica particles is 1.0 or more, the polishing rate of the polished body represented by the silicon wafer is excellent, and the productivity of the silicon wafer is excellent. In addition, if the agglomeration ratio of the silica particles is 4.0 or less, the surface roughness and damage of the polished body represented by the silicon wafer during polishing can be reduced, and the agglomeration of the silica particles can be suppressed.
[0107] The aggregation ratio of the silica particles was calculated using the following formula (12) from the average primary particle size measured by the above-mentioned measurement method and the average secondary particle size measured by the above-mentioned measurement method.
[0108] Agglomeration ratio = average secondary particle size / average primary particle size (12)
[0109] The metal impurity content of the silica particles is preferably 5 ppm or less, and more preferably 2 ppm or less. In this specification, ppm means mass ppm.
[0110] When grinding silicon wafers for semiconductor devices, metal impurities adhere to and contaminate the surface of the object being ground, thereby adversely affecting the properties of the wafer. Furthermore, metal impurities diffuse inside the wafer, degrading its quality. As a result, the performance of semiconductor devices manufactured from such wafers is significantly reduced.
[0111] In addition, if there are metal impurities in the silica particles, the acidic surface silanol groups will interact with the metal impurities in a coordinated manner, changing the chemical properties of the surface silanol groups (acidity, etc.) or changing the three-dimensional environment of the silica particle surface (ease of aggregation of silica particles, etc.), thereby affecting the polishing rate.
[0112] The metal impurity content of silica particles is measured by high-frequency inductively coupled plasma mass spectrometry (ICP-MS). Specifically, a silica sol containing 0.4 g of silica particles is accurately weighed, sulfuric acid and hydrofluoric acid are added, heated, dissolved and evaporated, and pure water is added to the remaining sulfuric acid drops in such a way that the total amount accurately reaches 10 g to prepare a test solution, which is measured using a high-frequency inductively coupled plasma mass spectrometer. The metals of the object are set as sodium, potassium, iron, aluminum, calcium, magnesium, zinc, cobalt, chromium, copper, manganese, lead, titanium, silver, and nickel, and the total content of these metals is set as the metal impurity content.
[0113] The metal impurity content of the silica particles can be set to 5 ppm or less by obtaining the silica particles by subjecting alkoxysilane as a main raw material to a hydrolysis reaction and a condensation reaction.
[0114] In the method of deionizing an alkali metal silicate such as water glass, sodium and the like derived from the raw material remain, and therefore it is extremely difficult to adjust the metal impurity content of the silica particles to 5 ppm or less.
[0115] As the shape of the silica particles, for example, spherical, chain-like, cocoon-like (also called tumor-like, peanut-like), irregular shapes (such as protrusion-like, curved, branch-like, etc.), etc. Among these shapes of silica particles, spherical is preferred when it is desired to reduce the surface roughness and damage of the object to be polished represented by silicon wafers during polishing, and irregular shapes are preferred when it is desired to further increase the polishing rate for the object to be polished represented by silicon wafers.
[0116] The silica particles according to the present embodiment preferably have no pores in view of excellent mechanical strength and storage stability.
[0117] The presence or absence of pores in the silica particles was confirmed by BET multipoint analysis using an adsorption isotherm with nitrogen as the adsorption gas.
[0118] In view of excellent mechanical strength and storage stability, the silica particles according to the present embodiment preferably have an alkoxysilane condensate as the main component, and more preferably a tetraalkoxysilane condensate as the main component. The so-called main component refers to 50% by mass or more of all components constituting the silica particles.
[0119] As tetraalkoxysilane condensates, for example, condensates of tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetraisopropoxysilane, etc. can be cited. These tetraalkoxysilane condensates can be used alone or in combination of two or more. Among these tetraalkoxysilane condensates, tetramethoxysilane condensates and tetraethoxysilane condensates are preferred, and tetramethoxysilane condensates are more preferred, from the viewpoint of fast hydrolysis reaction, difficulty in residual unreacted products, excellent productivity, and ability to easily obtain stable silica sol.
[0120] In order to obtain silica particles with alkoxysilane condensate as the main component, alkoxysilane is preferably used as the main raw material. In order to obtain silica particles with tetraalkoxysilane condensate as the main component, tetraalkoxysilane is preferably used as the main raw material. The so-called main raw material refers to 50% by mass or more of all the raw materials constituting the silica particles.
[0121] (Method for producing silicon dioxide particles)
[0122] As a method for producing silica particles, for example, a method by thermal decomposition of silicon tetrachloride, a method by deionization of alkali metal silicates such as water glass, a method by hydrolysis reaction and condensation reaction of alkoxysilane, etc. can be cited. Among these methods for producing silica particles, a method by hydrolysis reaction and condensation reaction of alkoxysilane is preferred because it can reduce the content of metal impurities and easily control the shape of silica particles. A method by hydrolysis reaction and condensation reaction of tetraalkoxysilane is more preferred.
[0123] As tetraalkoxysilane, for example, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetraisopropoxysilane, etc. can be cited. These tetraalkoxysilanes can be used alone or in combination of two or more. Among these tetraalkoxysilanes, tetramethoxysilane and tetraethoxysilane are preferred, and tetramethoxysilane is more preferred, from the viewpoint of fast hydrolysis reaction, difficulty in residual unreacted products, excellent productivity, and ability to easily obtain stable silica sol.
[0124] The raw materials constituting the silica particles may also be raw materials other than tetraalkoxysilane, such as low condensates of tetraalkoxysilane. In view of excellent reactivity, among all the raw materials constituting the silica particles, preferably, tetraalkoxysilane accounts for 50% by mass or more and raw materials other than tetraalkoxysilane account for 50% by mass or less, and more preferably, tetraalkoxysilane accounts for 90% by mass or more and raw materials other than tetraalkoxysilane account for 10% by mass or less.
[0125] The solvent or dispersion medium used in the reaction when carrying out hydrolysis reaction and condensation reaction can enumerate such as water, methanol, ethanol, propanol, isopropanol, ethylene glycol etc. These solvents or dispersion mediums can be used alone or in combination with more than two kinds. In these solvents or dispersion mediums, the material used in hydrolysis reaction and condensation reaction is the same as the material of by-product and the convenience of manufacturing is excellent, preferably water, alcohol, more preferably water, methanol.
[0126] The hydrolysis reaction and the condensation reaction may be carried out in the presence of a catalyst or in the absence of a catalyst. However, the presence of a catalyst is preferred from the viewpoint of promoting the hydrolysis reaction and the condensation reaction.
[0127] Examples of the catalyst include acid catalysts such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, formic acid, and citric acid, and base catalysts such as ethylenediamine, diethylenetriamine, triethylenetetramine, ammonia, urea, ethanolamine, and tetramethylammonium hydroxide. Among these catalysts, base catalysts are preferred from the perspectives of excellent catalytic action and easy control of particle shape, and base catalysts are preferred from the perspectives of being able to suppress the incorporation of metal impurities, having high volatility, and excellent removability after the condensation reaction, and ammonia is more preferred.
[0128] In order to increase the condensation degree of the silica particles, in the method for producing the silica particles according to the present embodiment, it is preferred that the silica particles obtained be subjected to a pressure heating treatment after the hydrolysis reaction and condensation reaction of the alkoxysilane are completed.
[0129] The pressure of the pressurized heat treatment is preferably 0.10 MPa or more, more preferably 0.14 MPa or more, and preferably 2.3 MPa or less, more preferably 1.0 MPa or less. If the pressure of the pressurized heat treatment is 0.10 MPa or more, the condensation degree of the silica particles can be increased. In addition, if the pressure of the pressurized heat treatment is 2.3 MPa or less, the silica particles can be manufactured without significantly changing the average primary particle size, the average secondary particle size, the cv value, and the agglomeration ratio, and the dispersion stability of the silica sol is excellent.
[0130] The temperature of the pressurized heat treatment is preferably 100° C. or higher, more preferably 110° C. or higher, and preferably 220° C. or lower, more preferably 180° C. or lower. If the temperature of the pressurized heat treatment is 100° C. or higher, the condensation degree of the silica particles can be increased. If the temperature of the pressurized heat treatment is 220° C. or lower, the silica particles can be produced without significantly changing the average primary particle size, the average secondary particle size, the cv value, and the agglomeration ratio, and the dispersion stability of the silica sol is excellent.
[0131] The time of the pressurized heat treatment is preferably 0.25 hours or more, more preferably 0.5 hours or more, and preferably 6 hours or less, more preferably 4 hours or less. If the time of the pressurized heat treatment is 0.25 hours or more, the condensation degree of the silica particles can be increased. If the time of the pressurized heat treatment is 6 hours or less, the silica particles can be manufactured without significantly changing the average primary particle size, the average secondary particle size, the cv value, and the agglomeration ratio, and the dispersion stability of the silica sol is excellent.
[0132] The pressurized heat treatment can be carried out in air or in a solvent or a dispersion medium. In view of the excellent dispersion stability of silica sol, it is preferably carried out in a solvent or a dispersion medium. In view of being able to accurately control the d value and the surface silanol group density without significantly changing the average primary particle size, the average secondary particle size, the cv value, and the agglomeration ratio, it is more preferably carried out in an aqueous dispersion.
[0133] The pressurized heat treatment can be carried out immediately after the hydrolysis reaction and the condensation reaction are completed, or it can be carried out after removing unnecessary components and adding necessary components from the components in the reaction liquid after the hydrolysis reaction and the condensation reaction. In view of being able to maintain a low operating pressure, it is preferably carried out after removing unnecessary components and adding necessary components from the components in the reaction liquid after the hydrolysis reaction and the condensation reaction, and it is more preferably carried out after removing the organic compound and adding water.
[0134] The pH during the pressurized heat treatment in the aqueous dispersion is preferably 6.0 or more, more preferably 6.5 or more, and preferably 8.0 or less, more preferably 7.8 or less. If the pH during the pressurized heat treatment in the aqueous dispersion is 6.0 or more, the gelation of the silica sol can be suppressed. In addition, if the pH during the pressurized heat treatment in the aqueous dispersion is 8.0 or less, the structural damage caused by dissolution can be prevented, and the d value and the surface silanol group density can be accurately controlled without significantly changing the average primary particle size, the average secondary particle size, the cv value, and the agglomeration ratio, and the aggregation of the silica particles can be suppressed, and the dispersion stability of the silica sol is excellent.
[0135] (Silica Sol)
[0136] The silica sol according to the present embodiment preferably contains the silica particles according to the present embodiment and a solvent or a dispersion medium.
[0137] The solvent or dispersion medium of the silica sol can be, for example, water, methanol, ethanol, propanol, isopropanol, ethylene glycol, etc. These solvents or dispersion mediums of the silica sol can be used alone or in combination of two or more. Among these solvents or dispersion mediums of the silica sol, water and alcohol are preferred, and water is more preferred, in view of their excellent affinity with the silica particles.
[0138] The content of silica particles in the silica sol is preferably 3% by mass or more, more preferably 4% by mass or more, and further preferably 5% by mass or more in the total amount of the silica sol. In addition, it is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less. If the content of silica particles in the silica sol is 3% by mass or more, the polishing rate for the polished body represented by the silicon wafer is excellent. In addition, if the content of silica particles in the silica sol is 50% by mass or less, the aggregation of silica particles in the silica sol and the polishing composition can be suppressed, and the storage stability of the silica sol and the polishing composition is excellent.
[0139] The content of the solvent or dispersion medium in the silica sol is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more in the total amount of the silica sol. In addition, it is preferably 97% by mass or less, more preferably 96% by mass or less, and further preferably 95% by mass or less. If the content of the solvent or dispersion medium in the silica sol is 50% by mass or more, the aggregation of the silicon dioxide particles in the silica sol and the abrasive composition can be suppressed, and the storage stability of the silica sol and the abrasive composition is excellent. In addition, if the content of the solvent / dispersion medium in the silica sol is 97% by mass or less, the polishing rate of the polished body represented by the silicon wafer is excellent.
[0140] The content of the silica particles, solvent or dispersion medium in the silica sol can be set to a desired range by removing unnecessary components and adding necessary components from the components in the reaction solution after the hydrolysis reaction and the condensation reaction are completed.
[0141] The silica sol involved in this embodiment may contain, in addition to silica particles and a solvent or a dispersion medium, other components such as an oxidant, a preservative, a mildew preventer, a pH adjuster, a pH buffer, a surfactant, a chelating agent, an antibacterial / biocide, etc. as needed within a range that does not impair its performance.
[0142] In particular, from the viewpoint of excellent storage stability of silica sol, it is preferred that an antimicrobial / biocide be contained in the silica sol.
[0143] Examples of the antimicrobial / biocide include hydrogen peroxide, ammonia, quaternary ammonium hydroxide, quaternary ammonium salts, ethylenediamine, glutaraldehyde, methyl parahydroxybenzoate, sodium chlorite, etc. These antimicrobial / biocide may be used alone or in combination of two or more. Among these antimicrobial / biocide, hydrogen peroxide is preferred due to its excellent affinity with silica sol.
[0144] Biocides also include substances commonly referred to as fungicides.
[0145] The content of the antimicrobial / biocide in the silica sol is preferably 0.0001% by mass or more, more preferably 0.001% by mass or more, and preferably 10% by mass or less, more preferably 1% by mass or less, in the total amount of the silica sol. If the content of the antimicrobial / biocide in the silica sol is 0.0001% by mass or more, the storage stability of the silica sol is excellent. If the content of the antimicrobial / biocide in the silica sol is 10% by mass or less, the original performance of the silica sol is not impaired.
[0146] The pH of the silica sol is preferably 6.0 or more, more preferably 6.5 or more, and preferably 8.0 or less, more preferably 7.8 or less. If the pH of the silica sol is 6.0 or more, the long-term storage stability of the silica sol is excellent. If the pH of the silica sol is 8.0 or less, the aggregation of the silica particles can be suppressed, and the dispersion stability of the silica sol is excellent.
[0147] The pH of the silica sol can be adjusted to a desired range by adding a pH adjuster.
[0148] (Method for producing silica sol)
[0149] The silica sol according to the present embodiment may be produced by using the reaction solution after the hydrolysis reaction and the condensation reaction are completed as it is, or by removing unnecessary components from the components in the reaction solution after the hydrolysis reaction and the condensation reaction are completed and adding necessary components.
[0150] The production of silica sol may include a filtration step in order to remove coarse particles or avoid aggregation of fine particles.
[0151] Examples of the filtration method include natural filtration under normal pressure, reduced pressure filtration, pressure filtration, centrifugal filtration, and the like.
[0152] Filtration may be performed at any time and any number of times, but is preferably performed immediately before preparing the polishing composition from the viewpoint of excellent storage stability and polishing properties of the polishing composition.
[0153] (Abrasive composition)
[0154] The polishing composition according to this embodiment preferably contains the silica sol according to this embodiment and further contains a water-soluble polymer.
[0155] The water-soluble polymer improves the wettability of the polishing composition to the polished body represented by the silicon wafer. The water-soluble polymer is preferably a polymer having a functional group with high water affinity, and the functional group with high water affinity has high affinity with the surface silanol group of the silica particles, and the silica particles and the water-soluble polymer are stably dispersed at a closer position in the polishing composition. Therefore, when the polished body represented by the silicon wafer is polished, the effects of the silica particles and the water-soluble polymer work synergistically.
[0156] Examples of the water-soluble polymer include cellulose derivatives, polyvinyl alcohol, polyvinyl pyrrolidone, copolymers having a polyvinyl pyrrolidone skeleton, and polymers having a polyoxyalkylene structure.
[0157] Examples of the cellulose derivative include hydroxyethyl cellulose, hydroxyethyl cellulose subjected to hydrolysis treatment, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, and carboxymethyl cellulose.
[0158] Examples of the copolymer having a polyvinyl pyrrolidone skeleton include a graft copolymer of polyvinyl alcohol and polyvinyl pyrrolidone.
[0159] Examples of the polymer having a polyoxyalkylene structure include polyoxyethylene, polyoxypropylene, and a copolymer of ethylene oxide and propylene oxide.
[0160] These water-soluble polymers can be used alone or in combination of two or more. Among these water-soluble polymers, cellulose derivatives are preferred, and hydroxyethyl cellulose is more preferred, from the viewpoint of high affinity with the surface silanol groups of the silica particles and synergistic effect to impart good hydrophilicity to the surface of the body to be ground.
[0161] The mass average molecular weight of the water-soluble polymer is preferably 1,000 or more, more preferably 5,000 or more, further preferably 10,000 or more, and preferably 3,000,000 or less, more preferably 2,000,000 or less, and further preferably 1,000,000 or less. If the mass average molecular weight of the water-soluble polymer is 1,000 or more, the hydrophilicity of the polishing composition is improved. In addition, if the mass average molecular weight of the water-soluble polymer is 3,000,000 or less, the affinity with the silica sol is excellent, and the polishing rate for the polished body represented by the silicon wafer is excellent.
[0162] The mass average molecular weight of the water-soluble polymer was measured by size exclusion chromatography using a 0.1 mol / L NaCl solution as a mobile phase in terms of polyethylene oxide.
[0163] The content of the water-soluble polymer in the abrasive composition is preferably 0.02% by mass or more, more preferably 0.05% by mass or more, and preferably 10% by mass or less, more preferably 5% by mass or less, in the total amount of the abrasive composition. If the content of the water-soluble polymer in the abrasive composition is 0.02% by mass or more, the hydrophilicity of the abrasive composition is improved. In addition, if the content of the water-soluble polymer in the abrasive composition is 10% by mass or less, the aggregation of silica particles can be suppressed when the abrasive composition is prepared.
[0164] The grinding composition involved in this embodiment may contain, in addition to silica sol and water-soluble polymers, other ingredients such as alkaline compounds, grinding accelerators, surfactants, hydrophilic compounds, preservatives, mildew inhibitors, pH adjusters, pH buffers, surfactants, chelating agents, antibacterial / biocides, etc. as needed within the range that does not impair its performance.
[0165] In particular, it is preferred that the polishing composition contain a basic compound because it can chemically act on the surface of the polished object represented by a silicon wafer to perform chemical polishing (chemical etching) and utilize a synergistic effect with the surface silanol groups of the silica particles to increase the polishing rate of the polished object represented by a silicon wafer.
[0166] As the basic compound, for example, organic basic compounds, alkali metal hydroxides, alkali metal bicarbonates, alkali metal carbonates, ammonia, etc. can be listed. One of these basic compounds can be used alone, or two or more can be used in combination. Among these basic compounds, from the perspective of high water solubility and excellent affinity with silica particles and water-soluble polymers, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonium bicarbonate, and ammonium carbonate are preferred, and ammonia, tetramethylammonium hydroxide, and tetraethylammonium hydroxide are more preferred, and ammonia is further preferred.
[0167] The content of the basic compound in the abrasive composition is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, in the total amount of the abrasive composition. If the content of the basic compound in the abrasive composition is 0.001% by mass or more, the polishing rate of the polished body represented by the silicon wafer can be increased. In addition, if the content of the basic compound in the abrasive composition is 5% by mass or less, the stability of the abrasive composition is excellent.
[0168] The pH of the abrasive composition is preferably 8.0 or more, more preferably 9.0 or more, and preferably 12.0 or less, more preferably 11.0 or less. If the pH of the abrasive composition is 8.0 or more, the agglomeration of the silica particles in the abrasive composition can be suppressed, and the dispersion stability of the abrasive composition is excellent. In addition, if the pH of the abrasive composition is 12.0 or less, the dissolution of the silica particles can be suppressed, and the stability of the abrasive composition is excellent.
[0169] The pH of the polishing composition can be adjusted to a desired range by adding a pH adjuster.
[0170] The polishing composition according to the present embodiment can be obtained by mixing the silica sol according to the present embodiment with a water-soluble polymer and other components as required. However, in consideration of storage and transportation, the polishing composition may be prepared at a high concentration and diluted with water or the like immediately before polishing.
[0171] (use)
[0172] The silica particles involved in this embodiment, the silica particles obtained by the production method involved in this embodiment, the silica sol involved in this embodiment, and the polishing composition involved in this embodiment can be suitably used for polishing purposes, and can be used for, for example, polishing of semiconductor materials such as silicon wafers, polishing of electronic materials such as hard disk substrates, polishing in the planarization process when manufacturing integrated circuits (chemical mechanical polishing), polishing of photomasks, synthetic quartz glass substrates used in liquid crystals, polishing of magnetic disk substrates, etc., among which they are particularly suitable for polishing silicon wafers and chemical mechanical polishing.
[0173] (Grinding method)
[0174] The polishing method according to the present embodiment is preferably a method of polishing using the polishing composition according to the present embodiment.
[0175] As a specific polishing method, for example, there is a method in which the surface of the silicon wafer is pressed against a polishing pad, the polishing composition according to the present embodiment is dropped onto the polishing pad, and the surface of the silicon wafer is polished.
[0176] (Method for manufacturing semiconductor wafer)
[0177] The method for producing a semiconductor wafer according to the present embodiment is a method including the step of polishing using the polishing composition according to the present embodiment, and the specific polishing method is as described above.
[0178] Examples of the semiconductor wafer include a silicon wafer and a compound semiconductor wafer.
[0179] (Method for manufacturing semiconductor device)
[0180] The method for manufacturing a semiconductor device according to the present embodiment is a method including the step of polishing using the polishing composition according to the present embodiment, and the specific polishing method is as described above.
[0181] Example
[0182] The present invention will be further specifically described below using examples, but the present invention is not limited to the description of the following examples within the scope of the present invention.
[0183] (Measurement of average primary particle size)
[0184] The silica sols containing silica particles obtained in Examples and Comparative Examples were freeze-dried, and the specific surface area of the silica particles was measured using an automatic specific surface area measuring device "FlowSorb II" (model name, manufactured by Shimadzu Corporation). The density was set to 2.2 g / cm using the following formula (10): 3 , calculate the average primary particle size.
[0185] Average primary particle size (nm) = 6000 / (specific surface area (m 2 / g)×density(g / cm 3 ))···(10)
[0186] (Measurement of average secondary particle size and cv value)
[0187] The average secondary particle size of the silica sols containing silica particles obtained in Examples and Comparative Examples was measured using a dynamic light scattering particle size analyzer "Zetasizer Nano ZS" (model name, manufactured by Malvern), and the cv value was calculated using the following formula (11).
[0188] cv value = (standard deviation (nm) / average secondary particle size (nm)) × 100... (11)
[0189] (Calculation of Agglomeration Ratio)
[0190] The agglomeration ratio was calculated from the measured average primary particle size and average secondary particle size using the following formula (12).
[0191] Agglomeration ratio = average secondary particle size / average primary particle size (12)
[0192] (Determination of d value)
[0193] Using an X-ray diffraction apparatus (model name "RINT-UltimaIII", manufactured by Rigaku Corporation), the silica sol containing silica particles obtained in the examples and comparative examples was filled into the recessed part of a silicon non-reflective sample plate and installed in the apparatus. A copper X-ray tube with an output power of 1.5 kW was applied at 40 kV and 30 mA. On the side of the incident X-ray, a multilayer film mirror and a Soller slit with an opening angle of 5° were set for parallelizing, compressing, and monochromatizing the X-rays. On the side of receiving the X-rays, a long parallel slit with an opening angle of 0.114° and a scintillation counter were set. The silica sol on the non-reflective sample plate was irradiated with copper Kα rays (the wavelength of Kα1 rays is 0.1°) at an irradiation angle of 0.1°. ) is used as a parallel beam, and 2θ scanning (2θ range is 5° to 50°) is performed to obtain an X-ray scattering pattern. The scattering angle 2θ showing the maximum intensity of the obtained halo pattern is recorded, and the scattering vector q (q = 4π·sinθ / λ) is calculated. Using the scattering vector q, the d value is calculated using the following formula (5) representing the Bragg formula (λ = 2d·sinθ).
[0194] d=2π / q···(5)
[0195] (Determination of surface silanol group density)
[0196] The silica sol containing silica particles obtained in Examples and Comparative Examples was collected in an amount corresponding to 1.5 g of silica particles in a 200 mL tall beaker, and pure water was added to adjust the liquid volume to 90 mL.
[0197] In an environment of 25°C, insert a pH electrode into a tall beaker and stir the test solution for 5 minutes using a magnetic stirrer. While continuing to stir with a magnetic stirrer, add a 0.1 mol / L hydrochloric acid aqueous solution until the pH reaches 3.6. Remove the pH electrode from the tall beaker, and while continuing to stir with a magnetic stirrer, add 30 g of sodium chloride, and slowly add pure water to completely dissolve the sodium chloride. Add pure water until the total amount of the final test solution reaches 150 mL, and stir the test solution with a magnetic stirrer for 5 minutes to obtain the test solution.
[0198] The tall beaker containing the obtained test solution was placed in an automatic titration device "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.), and the pH electrode and burette attached to the device were inserted into the tall beaker. While stirring the test solution with a magnetic stirrer, a 0.1 mol / L sodium hydroxide aqueous solution was added dropwise through the burette, and the titration amount A (mL) of the 0.1 mol / L sodium hydroxide aqueous solution required to reach pH from 4.0 to 9.0 was measured.
[0199] The consumption V (mL) of 0.1 mol / L sodium hydroxide aqueous solution required to increase the pH of 1.5 g of silica particles from 4.0 to 9.0 was calculated using the following formula (6). The surface silanol group density ρ (number / nm) of silica particles was calculated using the following formula (7). 2 ).
[0200] V=(A×f×100×1.5) / (W×C)···(6)
[0201] A: The titration amount of 0.1 mol / L sodium hydroxide aqueous solution required to increase the pH from 4.0 to 9.0 for 1.5 g of silica particles (mL)
[0202] f: Titer of the 0.1 mol / L sodium hydroxide aqueous solution used
[0203] C: Concentration of silica particles in silica sol (mass %)
[0204] W: The amount of silica sol collected (g)
[0205] ρ=(B×N A ) / (10 18 ×M×S BET )···(7)
[0206] B: The amount of sodium hydroxide (mol) required to adjust the pH of 1.5 g of silica particles from 4.0 to 9.0, calculated from V
[0207] N A : Avogadro constant (unit / mol)
[0208] M: Silica particle amount (1.5 g)
[0209] S BET : Specific surface area of silica particles measured when calculating the average primary particle size (m 2 / g)
[0210] (Determination of metal impurity content)
[0211] Silica sol containing 0.4 g of the silica particles obtained in Comparative Example 1 was accurately weighed, sulfuric acid and hydrofluoric acid were added, heated, dissolved and evaporated, and pure water was added to the remaining sulfuric acid drops in such a way that the total amount accurately reached 10 g to prepare a test solution, and the metal impurity content was measured using a high-frequency inductively coupled plasma mass spectrometer "ELEMENT2" (model name, manufactured by Thermo Fisher Scientific).
[0212] The metal impurity content in the silica particles was 1.1 ppm for sodium, 0.140 ppm for potassium, 0.015 ppm for iron, 0.135 ppm for aluminum, 0.075 ppm for calcium, 0.07 ppm for zinc, and less than 0.005 ppm for magnesium, cobalt, chromium, copper, manganese, lead, titanium, silver, and nickel.
[0213] Therefore, it is considered that the metal impurity content in the silica particles of Examples 1 to 7 and Comparative Examples 2 and 3 is 5 ppm or less.
[0214] (Storage stability)
[0215] The silica particles obtained in Examples and Comparative Examples were visually checked for sedimentation one year after purchase or production to evaluate storage stability.
[0216] The case where no sedimentation of silica particles was observed with the naked eye was considered to have good storage stability, which was indicated by "A" in the table. The case where both sedimentation of silica particles could be observed and the case where no sedimentation of silica particles was observed were considered to have medium storage stability, which was indicated by "B" in the table. The case where a large amount of silica particles precipitated was considered to have no storage stability, which was indicated by "C" in the table.
[0217] [Comparative Example 1]
[0218] Tetramethoxysilane and methanol were mixed at a volume ratio of 3:1 to prepare a raw material solution. A reaction solvent containing a mixture of methanol, pure water, and ammonia was pre-charged in a reaction tank equipped with a thermometer, a stirrer, a supply pipe, and a distillation line. The concentration of water in the reaction solvent was 15% by mass, and the concentration of ammonia in the reaction solvent was 1% by mass.
[0219] The temperature of the reaction solvent was maintained at 20°C, and the reaction solvent and the raw material solution were set to 9.2:1 (volume ratio), and the raw material solution was dripped into the reaction tank at a uniform rate over 25 minutes to obtain a silica sol. Pure water was added to the obtained silica sol to adjust the liquid volume so that the content of silica particles became about 20% by mass, and the temperature was increased to remove methanol and ammonia, thereby obtaining a silica sol with a content of silica particles of about 20% by mass.
[0220] Table 1 shows the evaluation results of the obtained silica particles.
[0221] [Examples 1 to 7 and Comparative Examples 2 and 3]
[0222] The silica sol obtained in Comparative Example 1 was subjected to a pressure heat treatment under the conditions shown in Table 1 to obtain a silica sol having a silica particle content of approximately 20% by mass.
[0223] The evaluation results of the silica particles contained in the obtained silica sol are shown in Table 1. In the table, "-" indicating the physical properties of the particles of Comparative Examples 2 and 3 means that the particles could not be measured due to significant aggregation.
[0224] [Comparative Example 4]
[0225] Commercially available silica sol (trade name "PL-3", manufactured by Fuso Chemical Industries, Ltd.) was used as it was.
[0226] Table 1 shows the evaluation results of the silica particles contained in the silica sol.
[0227] [Table 1]
[0228]
[0229] As shown in Table 1, compared with Comparative Example 1 which was not subjected to pressure and heat treatment and Comparative Example 4 which was unclear whether pressure and heat treatment was performed, the average primary particle size, average secondary particle size, cv value, and agglomeration ratio of the silica particles in the silica sols obtained in Examples 1 to 7 which were subjected to pressure and heat treatment were almost unchanged, and the d value was improved, and Formula (1) was established. The establishment of Formula (1) indicates the formation of a larger ring than the commercially available silica particles such as Comparative Example 4, which means that by sharing SiO 4 The ring formation that tetrahedral oxygen carries out is promoted, and the defect of silicon dioxide particles is few.This means that 4-ring is few, so deformation is few, and it is difficult for elastic deformation, so it can be expected that the mechanical strength of silicon dioxide particles is excellent, the grinding characteristics of grinding composition are excellent.In addition, owing to carrying out pressurized heat treatment, it is therefore believed that the content of alkoxyl group and silanol group has reduced, and reactive sites are few, and it can be expected that the storage stability of silica sol is also excellent.In addition, it is believed that the greater the d value, the smaller the true specific gravity usually as silicon oxygen mineral, so it can be expected that the stable silicon dioxide particles that are difficult for sedimentation have been formed.
[0230] In Comparative Example 2 in which the pressure heat treatment was performed but the treatment was performed under alkaline conditions and Comparative Example 3 in which the treatment was performed under acidic conditions, the silica particles were significantly aggregated and a large amount of silica particles precipitated, and the d value and the surface silanol group density could not be measured.
[0231] In Comparative Example 4, which is a commercially available silica sol, it was observed that the silica particles sometimes precipitated and sometimes did not precipitate, and the storage stability was moderate.
[0232] In Comparative Example 1, which was not subjected to the pressurized heat treatment, although no precipitated silica particles were visually confirmed in this evaluation, it is believed that the content of alkoxy groups and silanol groups is higher than that of Examples 1 to 7, and the number of reactive active sites is higher, and precipitation of silica particles may occur when stored for a longer period of time.
[0233] Furthermore, in Comparative Examples 1 and 4, the d value is low and the formula (1) is not satisfied. The failure to satisfy the formula (1) is considered to be due to the failure to form a macrocyclic ring and the shared SiO 4 The tetrahedral oxygen-based ring formation is not promoted, and the silica particles have many defects. This means that there are many 4-membered rings, so there are many deformations and elastic deformations. Therefore, it is expected that the mechanical strength of the silica particles is poor and the polishing properties of the polishing composition are poor.
[0234] The present invention is described in detail with reference to specific embodiments, but it is clear to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on Japanese patent applications (Special Application 2019-029142) filed on February 21, 2019 and Japanese patent applications (Special Application 2019-029143) filed on February 21, 2019, the contents of which are incorporated herein by reference.
[0235] Industrial Applicability
[0236] The silica particles of the present invention, the silica particles obtained by the production method of the present invention, the silica sol of the present invention, and the polishing composition of the present invention can be suitably used for polishing purposes, and can be used for, for example, polishing of semiconductor materials such as silicon wafers, polishing of electronic materials such as hard disk substrates, polishing in the planarization process when manufacturing integrated circuits (chemical mechanical polishing), polishing of synthetic quartz glass substrates used in photomasks and liquid crystals, polishing of magnetic disk substrates, etc., and can be particularly suitably used for polishing of silicon wafers and chemical mechanical polishing.
Claims
1. A silicon dioxide particle, wherein the d value measured by wide-angle X-ray scattering is When , the following formula (1) is satisfied: y≥4.2 (1), The silicon dioxide particles are mainly composed of alkoxysilane condensate. The metal impurity content is less than 5 ppm.
2. The silica particles according to claim 1, wherein the surface silanol group density measured by the Sears method is x number / nm 2 When the d value and the surface silanol group density satisfy the following formula (2), y≥-0.2x+5.4 (2).
3. The silica particles according to claim 1 or 2, wherein the d value and the surface silanol group density measured by the Sears method are x / nm 2 The surface silanol group density further satisfies the following formula (3) and the following formula (4), y≤6.0 (3) y≤-0.2x+7.0 (4). The silica particles according to claim 1 or 2, wherein the average primary particle size measured by a BET method is 10 nm to 60 nm. 5 . The silica particles according to claim 1 , wherein the average secondary particle size measured by DLS method is 20 nm to 100 nm. The silica particles according to claim 1 or 2, comprising a tetraalkoxysilane condensate as a main component. 7 . The silica particles according to claim 6 , wherein the tetraalkoxysilane condensate comprises a tetramethoxysilane condensate. 8 . A method for producing silica particles, comprising subjecting silica particles to a pressure-heat treatment to obtain the silica particles according to claim 1 . 9 . A silica sol comprising the silica particles according to claim 1 . 10 . The silica sol according to claim 9 , wherein the content of the silicon dioxide particles in the total amount of the silica sol is 3% by mass to 50% by mass.
11. An abrasive composition comprising the silica sol according to claim 9 or 10.
12. A grinding method, comprising grinding using the grinding composition according to claim 11. 13 . A method for producing a semiconductor wafer, comprising a step of polishing using the polishing composition according to claim 11 . 14 . A method for manufacturing a semiconductor device, comprising a step of polishing using the polishing composition according to claim 11 .
Citation Information
Patent Citations
Vehicle using solar ray as power
JP1984067118A
High frequency heater
JP1985047395A
Production of cocoon-shaped colloidal silica
JP1999060232A
Silica particle dispersion and method for producing the same
JP2010083744A
Silica-based particles for polishing and abrasive
JP2018090798A